Algebraic and computer-based methods in the undirected degree/diameter problem - A brief survey - Hebert Perez-Roses (Electronic Journal of Graph Theory and Applications (EJGTA), 2014)
This paper discusses the most popular algebraic techniques and computational methods that have been used to construct large graphs with given degree and diameter.